2014
DOI: 10.5897/ajmr2013.6355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lactobacillus and Bacillus-based probiotics as alternatives to antibiotics in enteric microbial challenged weaned piglets

Abstract: The present study investigates the efficacies of two probiotic products as alternative to antibiotics on growth performance, nutrient digestibility, immunity, and fecal microbiota in piglets challenged with Salmonella enterica serovar Typhimurium KCTC 2515 and Escherichia coli KCTC 2571. Ninety-six 28-day-old piglets were randomly allotted to four dietary treatments consisting of four replicate pens with six piglets each. The dietary treatments were: negative control (NC), positive control (PC, 0.002% apramyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 35 publications
1
22
0
4
Order By: Relevance
“…Evidence suggests that probiotics and prebiotics could beneficially modify gut microbiota composition and activity in humans and animals (Barba-Vidal et al 2018; Moura et al 2007), thereby improving host metabolism and health, notably at the intestinal level. For example, the probiotics Lactobacillus ( Lactobacillus reuteri avibro ) and Bacillus ( Bacillus subtilis and Bacillus licheniformis ) exhibited the ability to increase nutrient digestibility and animal performance, and they reduced the abundance of pathogens ( Salmonella and Escherichia coli ) (Ahmed et al 2014). In pigs, some prebiotic products, such as xylo-oligosaccharides (XOS), β-mannanase, mannan-oligosaccharides, and yeast cultures have been used to modify gut microbiota composition, improve host immune response, stimulate the growth of more beneficial bacteria, and inhibit the colonization or abundance of pathogens by producing antimicrobial substances in humans and livestock (Barros et al 2015; De Maesschalck et al 2015; Liu et al 2018; Rastall and Gibson 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that probiotics and prebiotics could beneficially modify gut microbiota composition and activity in humans and animals (Barba-Vidal et al 2018; Moura et al 2007), thereby improving host metabolism and health, notably at the intestinal level. For example, the probiotics Lactobacillus ( Lactobacillus reuteri avibro ) and Bacillus ( Bacillus subtilis and Bacillus licheniformis ) exhibited the ability to increase nutrient digestibility and animal performance, and they reduced the abundance of pathogens ( Salmonella and Escherichia coli ) (Ahmed et al 2014). In pigs, some prebiotic products, such as xylo-oligosaccharides (XOS), β-mannanase, mannan-oligosaccharides, and yeast cultures have been used to modify gut microbiota composition, improve host immune response, stimulate the growth of more beneficial bacteria, and inhibit the colonization or abundance of pathogens by producing antimicrobial substances in humans and livestock (Barros et al 2015; De Maesschalck et al 2015; Liu et al 2018; Rastall and Gibson 2015).…”
Section: Introductionmentioning
confidence: 99%
“…b An R-value near + 1 means that there is dissimilarity between the groups, while an R-value near 0 indicates no significant dissimilarity between the groups. Sonia et al, 2014;Zheng et al, 2016;Upadhaya et al, 2017). This study observed a reduction of E. coli and ETEC toxins mainly in pigs supplied with host-adapted L. reuteri.…”
Section: Probiotic Activity Of Host Adapted and Nomadic Lactobacillimentioning
confidence: 51%
“…As noted by (Jacela et al, 2010;Ahmed et al, 2014;Fedak et al, 2018;Czech et al, 2018), most probiotics are based on different strains of lactic and bifidobacteria. Depending on the antagonistic properties of pathogenic and conditionally pathogenic microflora, appropriate strains are selected for composition of probiotic preparations.…”
Section: Discussionmentioning
confidence: 99%